A Factors Associated with the Incidence of Skin Diseases among Scavengers at Muara Fajar Landfill, Pekanbaru City in 2023: Faktor-faktor yang berhubungan dengan kejadian penyakit kulit pada pemulung di TPA mura fajar kota pekanbaru tahun 2023 - Deoni titriani indah sari Deoni; Elmia Kursani; Henny Maria Ulfa (Jurnal Olahraga dan Kesehatan (ORKES), 2023)
Tropical climate conditions in Indonesia increase the development of fungi that cause skin diseases, which is related to the high prevalence rate of skin diseases in Indonesia. Skin diseases are increasing, as evidenced by data from the Indonesian Ministry of Health in 2012. The prevalence of skin diseases in Indonesia was 8.46%, then increased in 2013 to 9% (Ministry of Health, 2013). According to Riskesdas data (2013), it also shows the high prevalence rate of skin diseases in Indonesia at 6.78%. Based on the results of an initial survey conducted by researchers through observations and interviews with 10 respondents who worked around the Muara Fajar TPA, 5 of them experienced skin health problems. The aim of this research is to determine the factors associated with the incidence of skin disease among scavengers at the Muara Fajar TPA, Pekanbaru City in 2023. This research method is quantitative analytical using a cross sectional research design. The sampling technique uses accidental sampling with a population of 250 people and a sample of 71 person. Data collection was carried out using questionnaires and observations. From the research results, it was found that factors related to the incidence of skin disease were length of service (P value= 0.027, POR = 8.850), use of PPE (P value = 0.009, POR = 8.813), length of work (P value = 0.001, POR = 9.000) , and environmental sanitation (P value= 0.127, POR = 5.971). It is recommended that scavengers increase awareness of the importance of using PPE in order to reduce the risk of skin diseases.